An unusual case of coronavirus disease 2019: Delayed chest CT evidence - Shi, Xiudong (J Infect Public Health, 2020)
Asymptomatic patients and infected patients with normal chest CT imaging are considered carriers of SARS-CoV-2. Before a diagnosis of coronavirus disease 2019 (COVID-19) is made, these patients with negative chest CT findings may be ignored, causing the possibility of virus transmission. For patients with suspected infections, reliable epidemiological information and clinical symptoms, clinical management is necessary even when the chest CT is negative.